KESUSASTRAAN MELAYU DAN PERANNYA DALAM DUNIA ISLAM NUSANTARA - Saiful Hakam (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2017)
Malay and Javanese literature are not separate from each other and many translate to each other. Both become very interesting research fields to be studied, studied, and discussed with greater accuracy, thoroughness and interest (Oberbeck, 1924: 38-43; 1930: 208-230). As is known, the stories of Panji are widely disseminated in Malay and even adapted into Siamese (Winstedt, 1972). Most notably, however, some of the normative, metaphysical or educative texts mentioned above and those expressing a change of mentality have been translated into Javanese. It is enough to refer to the lists in the Catalog of the Order of Th. Pigeaud to see for example that at various times has been adaptation of Tajul Salatin, some writings Hamzah Fansuri, Hikayat Bayan Budiman, Hikayat Iskandar zulkarnain, even from some Bab Bustanul Salatin. (Pigeaud, Poerbatjaraka, 1952